Nano-scaled semiconductor devices : physics, modelling and characterization - Gutierrez-D., Edmundo A. (Materials, circuits and devices series ;, 2016)
This book describes methods for the characterisation, modelling, and simulation prediction of these second order effects in order to optimise performance, energy efficiency and new uses of nano-scaled semiconductor devices.